Studi Empiris Analisis Perilaku Pembelian Online (Online Buying Behavior) Pada Konsumen Generasi Y Muslim Dengan Intention To Buy Sebagai Variabel Mediasi - Damayanti, Maretta Edgina; Djastuti, Indi (Jurnal Ilmiah Ekonomi Islam, 2023)
This research was carried out with the aim of an empirical study of analyzing online buying behavior in Generation Y consumers with intention to buy as a mediating variable. This study uses an explanatory research design with a causality approach. The population used is consumers from the millennial generation. referring to the Indonesian Central Statistics Agency (BPS) (2020) who were aged 21-36 years during the research period. The sample used in this study was 100-200 respondents. Data collection was carried out using a questionnaire. The results of this empirical test show that perceived enjoyment is proven to have a significant positive effect on intention to buy. This means that the higher the respondent's perception of perceived enjoyment, the stronger the respondent's intention to buy. The results show that the simplicity motive is proven to have a significant positive effect on intention to buy. This means that the simplicity motive underlies the intention to buy. The results of the study show that information abundance has been proven to have a significant positive effect on the intention to buy. Which means that changes in intention to buy are influenced by changes in information abundance. The results of this empirical study show that intention to buy is proven to have a significant positive effect on online buying behavior. This means that strengthening the intention to buy causes the growth of online buying behavior.